Large-grained oriented polycrystalline silicon thin films prepared by nickel-silicide-induced crystallization - Schmidt, Javier Alejandro (2008)
Nickel-silicide-induced crystallization of hydrogenated amorphous silicon thin films has been investigated. Intrinsic and doped films were deposited on glass substrates by HF-PECVD, and Ni was dc sputtered on top. Nucleation and growth of grains were followed by optical microscopy, scanning electron microscopy (SEM), UV reflectance and X-ray diffraction. Homogeneous, large and oriented grains, with diameters over 25 μm, were obtained in intrinsic and lightly boron-doped films. Phosphorous-doped films presented a random needle-like growing mechanism, instead of the disk shape shown by the other samples. The effect of doping elements on the crystallization process is discussed.